2010
DOI: 10.1016/j.drugalcdep.2010.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological evaluation of the natural constituent of Cannabis sativa, cannabichromene and its modulation by Δ9-tetrahydrocannabinol☆

Abstract: In contrast to the numerous reports on the pharmacological effects of Δ 9 -tetrahydrocannabinol (THC), the pharmacological activity of another substituent of Cannabis sativa, cannabichromene (CBC) remains comparatively unknown. In the present study, we investigated whether CBC elicits cannabinoid activity in the tetrad assay, which consists of the following four endpoints: hypomotility, antinociception, catalepsy, and hypothermia. Because cannabinoids are well documented to possess anti-inflammatory properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 43 publications
4
72
0
Order By: Relevance
“…in vivo to mice at the dose of 15 mg kg −1 , could at least modify the mRNA expression of these channels and evaluated the effect of this major cannabinoid on the levels of the mRNA encoding for TRPV1–4 channels in the jejunum and ileum. Given the pro‐inflammatory effects of TRP channels and the anti‐inflammatory effect of CBC (DeLong et al. 2010), we have also carried out these experiments in croton oil‐treated mice, in which there is inflammation of the upper gastrointestinal tract.…”
Section: Resultsmentioning
confidence: 99%
“…in vivo to mice at the dose of 15 mg kg −1 , could at least modify the mRNA expression of these channels and evaluated the effect of this major cannabinoid on the levels of the mRNA encoding for TRPV1–4 channels in the jejunum and ileum. Given the pro‐inflammatory effects of TRP channels and the anti‐inflammatory effect of CBC (DeLong et al. 2010), we have also carried out these experiments in croton oil‐treated mice, in which there is inflammation of the upper gastrointestinal tract.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, THCV was shown to antagonise some of the effects of THC in mice, such as analgesia and hypothermia, due to THCV behaving as a cannabinoid receptor antagonist (Pertwee et al, 2007). The co-administration of CBC with THC promoted additive effects on catalepsy, analgesia and inflammation in mice, which might be attributable to CBC enhancing the brain concentrations of THC (DeLong et al, 2010). Clearly more studies are needed in this area, to carefully evaluate the pros and cons of cannabinoid combination psychopharmacology, and assist in the development of medicinal cannabis and cannabinoid therapies.…”
Section: Individual Differences In Response To Cannabis: Contributmentioning
confidence: 99%
“…However, little is known about other non-CB 1 receptor mechanisms in cannabinoid action. We and others have recently reported that functional CB 2 receptors are also expressed in the brain (see a comprehensive review by Jordan & Xi, 2019) and are involved in multiple behavioural effects of Δ 9 -THC or other cannabinoids in experimental animals (DeLong, Wolf, Poklis, & Lichtman, 2010;Lesniak et al, 2019;Liu et al, 2017). Although, little is known if brain CB 2 receptors are also involved in cannabinoidinduced tetrad effects.…”
Section: Introductionmentioning
confidence: 99%